Korelasi Kadar Leptin Plasma Dengan Massa Ventrikel Kiri Pada Laki-Laki Normotensi - Richard Indra Gunawan; Adrianus Kosasih; Oktavia Lilyasari; Andang H Joesoef; RWM Kaligis (Jurnal Kardiologi Indonesia, 2007)
Background.Obesity is one of Cardiovascular risk factor. Obesity caused increase in heart mass due to cellular hypertrophic and metaplastic proses, independently of hemodynamic factors such as blood pressure. There were hyperleptinemia in obesity due to the selective Leptin resistency in central nervous system and peripheral organs. Study with cultured rat cardiomyocyte have shown hypertrophy and hyperplastic effect of Leptin to cardiomyocyte. Some clinical studies have shown correlation between circulating Leptin level with Left Ventricle Mass in hypertensive and insulin resistance men.Objective. This study aimed to elaborate the correlation between circu-lating Leptin level with Left Ventricle Mass in normotensive men.Methods. A cross sectional study was performed with normotensive men, which included 40 obese normotensive and 40 normoweight men. All patients underwent physical and laboratory assessment and examination of Left Ventricle with echocardiography. The circulating Leptin level were determined by ELISA method. The Leptin level were expressed as median (25th percentile; 75th percentile)Results. The circulating Leptin level were significantly different between the obese normotensive and the lean group. The Left Ventricle Mass in Obese increased, although have not fulfilled the criteria for Left Ventricle Hypertrophy. There were significant correlation between Left Ventricle Mass with BMI (r = 0,711; p<0,001) and waist circumference (r = 0,732; p<0,001). Respectively, there were significant correlation between Left Ventricle Mass Index with BMI (r = 0.541; p<0.001) and waist circumfer-ence (r = 0,558; p<0.001. There were significant correlation between circulating Leptin level with Left Ventricle Mass (r = 0,510; <0,001) and Left Ventricle Mass Index (r = 0,414; p<0,001) in obese men.Conclusion.Circulating Leptin level is correlated with Left Ventricle Mass in normotensive men.